Development of Video-Based Teaching Modules to Improve Science Learning Outcomes of Class V Students of SD Negeri 2 Peudawa East Aceh - Safhunna, Mutia; Sari, Siti Mayang; Rahmattullah, Rahmattullah; Syafii, Mhd. (Pascasarjana UM, 2024)
This research aims to develop a video-based teaching module to improve science and science learning outcomes for class V students. The development method used is Research and Development (R&D), namely using the ADDIE model to produce certain products and test the effectiveness of these products. This research involved 30 fifth grade students at SDN 2 Peudawa, East Aceh Regency and one teacher as respondents. The research instruments used were validation questionnaires and observation sheets. Analysis techniques are used to determine the feasibility of the video-based teaching modules that have been assessed. The results of the research show that the video-based teaching module developed has a level of validity, namely that it can be seen that the N-Gain Score means a mean value of 0.8685, this value is greater than 0.3 (0.89>0.3), so the category obtained is high / high effectiveness. N-Grain Percent mean value is 89.8035, this value is greater than 86% (89%>86%), so it is interpreted as effective. So it can be concluded that the teaching module developed is effective in improving students' science learning outcomes. The implication of this research is that the module developed can be used as an effective learning resource to improve student learning outcomes in science and science learning at SDN 2 Peudawa, East Aceh Regency. Apart from that, this research also contributes to the development of video-based teaching modules that meet the needs of today's times and global challenges.